The Development of Regional Dialect Locality Judgments and Language Attitudes Across the Life Span. Issue 4 (20th October 2017) - McCullough, Elizabeth A.; Clopper, Cynthia G.; Wagner, Laura
Abstract : The development of language attitudes and perception of talker regional background was investigated across the life span ( N  = 240, age range = 4–75 years). Participants rated 12 talkers on dimensions of geographic locality, status, and solidarity. Children could classify some dialects by locality by age 6–7 years and showed adult‐like patterns by age 8 years. Children showed adult‐like status ratings for some dialects by age 4–5 years but were not fully adult‐like until age 12 years. Solidarity ratings were more variable and did not exhibit a clear developmental trajectory, although some adult‐like patterns were in place by age 6–7 years. Locality ratings were a significant but modest predictor of attitude ratings, suggesting that geographic knowledge is one contributor to language attitudes throughout development.